2021
DOI: 10.1088/1361-6528/ac18a2
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a cobalt sulfide nanoparticle-embedded flexible carbon nanofiber membrane electrocatalyst for advanced lithium–sulfur batteries

Abstract: Both the sluggish redox kinetics and severe polysulfide shuttling behavior hinders the commercialization of lithium–sulfur (Li–S) battery. To solve these obstacles, we design a cobalt sulfide nanoparticle-embedded flexible carbon nanofiber membrane (denoted as CoS2@NCF) as sulfiphilic functional interlayer materials. The hierarchically porous structure of carbon nanofiber is conducive to immobilizing sulfur species and facilitating lithium-ion penetration. Moreover, electrocatalytic CoS2 nanoparticles can sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The“adsorption‐diffusion‐conversion” mechanism has already been proposed. [ 47–51 ] Polar materials have high adsorption and strong catalytic effect on LiPSs, but most of these components have poor electrical conductivity. Thus, a synergistic strategy of compounding polar materials with carbon materials is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The“adsorption‐diffusion‐conversion” mechanism has already been proposed. [ 47–51 ] Polar materials have high adsorption and strong catalytic effect on LiPSs, but most of these components have poor electrical conductivity. Thus, a synergistic strategy of compounding polar materials with carbon materials is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-sulfur batteries have attracted great attention in the next generation of electrochemical energy storage systems due to their high theoretical specific capacity (1675 mAh/g) and high theoretical energy density (2600 Wh/kg), low cost, and environmental friendliness [1-3]. However, the shuttle effect and slow REDOX kinetics of lithium polysulfides (LiPSs) lead to low sulfur utilization rate, short cycle life, poor rate performance, which hinder the application of Li-sulfur batteries [4][5][6][7][8]. It is found that transition metals and metal compounds can effectively promote the conversion of soluble long-chain polylithium sulfide to short-chain lithium sulfide, improve their reaction kinetics, and effectively inhibit the shuttle effect, so as to achieve good long-cycle performance and rate performance more effectively [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%